The Ethnology of the Khezhas and Khezha Grammar - (:unkn) unknown (Central Institute of Indian Languages Mysore, 2022)
This book gives an idea about the Khezha community's culture and practice and also presents a linguistic overview of the language.
Keywords: Khezha; Ethnology; Grammar; Bharatavani; Knowledge Through Indian Languages; Linguistics; English; Khezha